2012
DOI: 10.1111/j.2044-8309.2012.02095.x
|View full text |Cite
|
Sign up to set email alerts
|

Principles and popularity: The interplay of moral norms and descriptive norms in the context of volunteerism

Abstract: Can a moral norm be manipulated and if so, how does a manipulated moral norm interact with a descriptive norm to impact on behavioural intentions? The present research addressed these questions in three studies. Study 1a and 1b demonstrated the validity of a manipulation designed to activate a moral norm for volunteer activity. In Study 2, activating a moral norm for volunteering strengthened intentions to volunteer and inhibited intentions to conform to a descriptive norm. Conceptual and applied implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…Are they tapping related but distinct concepts? While generally thought of as distinct constructs, previous research has documented a strong relationship between descriptive and injunctive norms and moral judgements, with some work evening defined injunctive norms in terms of morality (Goldring & Heiphetz, 2020;Lindstrom et al, 2018;Russell et al, 2021;Smith & Masser, 2012;Zhang et al, 2022). Across studies we found a moderately strong association between injunctive norms and moral judgements, indicating they are measuring related but distinct beliefs.…”
Section: Relationship Between Injunctive Norms and Moral Judgementssupporting
confidence: 45%
“…Are they tapping related but distinct concepts? While generally thought of as distinct constructs, previous research has documented a strong relationship between descriptive and injunctive norms and moral judgements, with some work evening defined injunctive norms in terms of morality (Goldring & Heiphetz, 2020;Lindstrom et al, 2018;Russell et al, 2021;Smith & Masser, 2012;Zhang et al, 2022). Across studies we found a moderately strong association between injunctive norms and moral judgements, indicating they are measuring related but distinct beliefs.…”
Section: Relationship Between Injunctive Norms and Moral Judgementssupporting
confidence: 45%
“…It is possible that participants in the present study perceived the moral norm plus intention items in this manner. Our findings may suggest caution in measuring moral norms in future in QBE research (see also (Smith & Masser, 2012).…”
Section: Discussionmentioning
confidence: 86%
“…A similarly complex issue emerges with moral norms. Although identified as a significant predictor of nondonors’ intentions to donate , external attempts to increase a nondonors’ sense of personal obligation to donate may result in those individuals correcting for that perceived influence . In contrast, other key predictors of intention, such as attitudes and self‐efficacy, show more promise as targets for intervention.…”
Section: What Do We Know?mentioning
confidence: 99%